Impact of industrial effluent on selected grass species - Zahra Fatima Imtiaz; Muhammad Irfan Ashraf; Sana Khan; Muhammad Arif Goheer; Muhammad Khalid Rafiq; Hafiz Bashir Ahmad; Oytun Emre Sakıcı (Society of Eminent Biological Scientists, 2024)
Industrial wastewater contains a variety of substances such as organic carbon, salts and heavy metals, which along with arsenic (As), cadmium (Cd), lead (Pb) and nickel (Ni) are known to be highly toxic even in very low concentrations. This study was carried out to test the impact of industrial effluent from the Industrial Estate Islamabad, the capital city of Pakistan, on four local grass species of the Pothohar region, i.e., Panicum maximum (Mombasa grass), Cenchrus ciliaris (Dhaman grass), Cynodon dactylon (Khabbal grass) and Chloris gayana (Rhodes grass). These grasses were grown in tap water (T0), industrial effluent (T1), and in industrial effluent-tap water ratio (50:50; T2). The concentrations of As, Cd, Pb, and Ni accumulated by these grasses were appraised with inductively coupled plasma optical emission spectrometry (ICP-OES). All four grasses differed significantly in terms of their accumulation of different types of metal elements in the shoot and root organs. The analysis of industrial effluent, and root and shoot biomass samples of all four grasses did not have high amounts of heavy metals with reference to the levels of the metals documented by WHO. It is generally recommended that the effluents from the Industrial Estate Islamabad can be used with some caution for growing forage grasses including the four species tested in this study.
Keywords: Agricultural Impact; Pulp and paper industry; QH301-705.5; Environmental engineering; phytoremediation; Environmental science; Industrial effluent; Engineering; pollution; Biology (General); heavy metals; Biology; Water Science and Technology; water pollution; waste water; FOS: Environmental engineering; Integrated Water Resources Management; Agronomy; Effluent; Environmental Science; Physical Sciences; 11. Sustainability; 2. Zero hunger; 15. Life on land; 6. Clean water; 13. Climate action